Penerapan Balanced Scorecard Dalam Pengukuran Kinerja Pada BLUD UPT Angkutan Dinas Perhubungan Pemerintah Kota Bandung - Nurfahmiadi, Farhan; Nurmalina, Rina (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to determine the performance of BLUD UPT Transportation of Transportation Department City of Bandung using the Balanced Scorecard method based on four perspectives, namely financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This research uses quantitative methods with a descriptive analysis approach. The type of data uses subject and documentary data. The population in this study were employees of BLUD UPT Transportation Dishub Bandung City and the Community. Data testing uses validity and reliability tests. Data analysis methods in financial perspectives use the concept of value for money by analysis economic ratios, effectiveness ratios, and efficiency ratios, in non-financial perspectives using service quality (servqual) analysis. The results of the performance measurement research at BLUD UPT Transportation of the Bandung City Transportation Agency as measured using the Balanced Scorecard method from a financial perspective based on the concept of value for money in the economic ratio obtained a score of 54%, in the effectiveness ratio obtained a score of 62%, and in the efficiency ratio obtained a score of 96%. The results on the customer perspective obtained a score of 75%. The internal business process perspective obtained a score of 71%. The growth and learning perspective obtained a score of 70%.